Quantitative in Morphological Classification - M. N. Mamadjanova (International Journal on Integrated Education, 2022)
The article discusses the fundamentals of morphological categorization as well as the relationship between quantitativeity and classification issues. Explanation of practical methods. In addition, the methods used in the fusion are examined.